Diagnostic value of circulating tumor cells in patients with thyroid cancer: a retrospective study of 1478 patients - Qingxin Zeng; Haifeng Zhong; Hui Rao; Yuedong Wang (Discover Oncology, 2024)
Abstract Background Circulating tumor cell (CTC) detection is one form of liquid biopsy. It is a novel technique that is beginning to be applied in the field of thyroid cancer. The present study was designed to evaluate the diagnostic value of CTCs in patients with thyroid cancer. Methods A total of 1478 patients were retrospectively analyzed and divided into malignant group (n = 747) and benign group (n = 731). Peripheral blood was collected, and CTCs were enriched and quantified before surgery. The baseline data of the two groups were matched by Propensity Score Matching (PSM). Receiver operating characteristic (ROC) curves were used to evaluate the diagnostic efficiency of different indicators for thyroid cancer. The malignant group before PSM was further divided into subgroups according to the BRAF V600E mutation and lymphatic metastasis (N stage), and the number of CTCs in different subgroups was compared. Results After 1:1 PSM, baseline characteristics of the malignant group and benign group were matched and assigned 315 cases in each group. The number of CTCs and the TPOAb values were comparable in the two groups (p > 0.05). The TgAb values [1.890 (1.110 – 16.010) vs 1.645 (1.030 – 7.073) IU/mL, p = 0.049] were significantly higher in the malignant group than in the benign group. After PSM, ROC analyses showed that the areas under the curve (AUCs) of CTC, TgAb and ultrasound were 0.537 (sensitivity 65.6%, specificity 45.8%), 0.546 (sensitivity 40.0%, specificity 70.8%) and 0.705 (sensitivity 77.1%, specificity 63.2%), respectively. The AUCs of the combined detection of ‘CTC + ultrasound’ (combine 1) and the combined detection of ‘CTC + TgAb + ultrasound’ (combine 2) were 0.718 (sensitivity 79.3%, specificity 61.7%) and 0.724 (sensitivity 78.0%, specificity 63.3%), respectively. The AUC of ultrasound was significantly higher than CTC (p < 0.001). There was no statistically significant difference in AUC between combination 1 and ultrasound, and between combination 2 and ultrasound (p > 0.05). The number of CTCs between the N0 and N1 subgroups, and between the BRAF mutant and BRAF wild subgroups was comparable (p > 0.05). Conclusions As an emerging and noninvasive testing tool, the efficacy of CTCs in diagnosing thyroid cancer is limited.